Groundwater, spring and interstitial Ostracoda (Crustacea) from Shiga Prefecture, Japan, including descriptions of three new species and one new genus - Smith, Robin J. (Zootaxa, 2011)
During surveys of a variety of groundwater, spring and interstitial habitats (e.g. in river bars, domestic wells, springs, and seeps) in Shiga Prefecture, Japan, a total of 15 ostracod species were recovered and identified. Three species and one genus are described for the first time herein, Undulacandona spinula n. gen & n. sp., Cryptocandona tsukagoshii n. sp. and Cavernocypris cavernosa n. sp.. Microdarwinula zimmeri (Menzel, 1916) is reported for the first time from Japan. Dolerocypris ikeyai Smith & Kamiya, 2006, Eucypris pigra (Fischer, 1851) and Cryptocandona brehmi (Klie, 1934) are new records for Shiga Prefecture.